Pemisahan POLRI Dari TNI Dan Implikasinya Terhadap Keamanan Dan Ketertiban Masyarakat Dl Daerah (Studi Kasus Di Kabupaten Cirebon Propinsi Jawa Barat) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The objective of this research is to study the effectiveness of the separation of the Indonesian Police Forces from the Indonesian Armed Forces policy application on the security and order of the people in the area. The research objects are the people's perception against Police's effort, sense of security, and the police and the armed forces relation. The population is society, policemen, and soldiers, with the samples are determined on a purposive sampling. The total samples are 200 citizens, 30 policemen from the Police Administrative of Cirebon Regency (I3olres Cirebon), and 60 soldiers from the Military District Command 0620 (Kodim 0620 / territorial unit) and 14 th Battalion of Air Defense Artillery (Batalyon Arhanudse 14 / battle support unit). The data are compiled with documentary, observation, interview and questionaires, and analysed in a descriptive-qualitative analysis. The research finding shows that more than two years after the separate policy application, the police's form a pattern and behavior (mentality) have not changed. They still have been applicating the old (pre-separation era) form a pattern and behavior (mentality). So the people's perception against the police's effort in security and social stability, law enforcement, and public service have not changed either (still low). In confronted with the improvement of the security disturbances, their work could not increase the people's sense of security yet. The separate policy just has implication on the structure of police and armed forces relation. In the functional relation, overlap in duty often happen, and in the personal, relation between the two institution more emotional than professional. So on the functional and personal relation between the police and the armed forces, the separation policy